The Role of Comorbid Conditions and Socioeconomic Factors in Mortality for Patients Hospitalized with COVID-19 - Roberta Redfern; Camelia Arsene; Lance Dworkin; Shipra Singh; Amala Ambati; Lukken Imel; Alexandria Williamson; Sadik Khuder (Ohio Journal of Public Health, 2023)
Background: The emergence of COVID-19 as a global pandemic has provided yet another example of how racial and social factors can exacerbate health disparities and disproportionately affect minority populations. The goal of the current study was to understand how some of these factors impacted survival in patients hospitalized with COVID-19 in Northwest Ohio during the first year of the pandemic. Methods: This study was a retrospective review of patient data from a single health care system. Electronic medical records were queried to obtain information on patients who were admitted to the hospital and had a laboratory-confirmed COVID-19 infection during their admission. Different predictors were included in the final Cox proportional hazard regression model. Results: There were 3468 patients included in the analyses with an all -cause mortality rate of 18.5%. On average, White patients were older on admission with higher rates of mortality than patients who were Black or of “Other” races (19.8% versus 12.5% and 11.0%, respectively, p < .001). Mortality rates varied significantly by insurance status, with the highest mortality rates observed in the Medicare and “Other” categories (27.1% and 16.5%, respectively). Cox proportional hazard regression model also found race and insurance status to be associated with survival. Conclusion: Considering race and preexisting conditions adjusted for age in a cohort of patients with COVID -19 reveals that insurance payor is significantly associated with mortality. Those who did not have commercial or public insurance had significantly increased risk of mortality compared to those with commercial insurance.
Keywords: All-cause mortality; Medicaid/Medicare; Social determinants of health; Socioeconomic status; Health disparities